A new constitutive model for high strength structural steels. (July 2021) - Wang, Yuan-Zuo; Kanvinde, Amit; Li, Guo-Qiang; Wang, Yan-Bo
Abstract: High Strength Structural (HSS) steels, with nominal yield strength greater than 450 MPa exhibit phenomena including Lode angle dependence of yield, and accelerated cyclic softening at large strains that cannot be conveniently simulated by existing constitutive models that are developed primarily for conventional strength structural steels. This paper presents an experimental study consisting of 25 coupon scale tests (monotonic and cyclic) as well as 2 large scale cantilever column tests. According to experimental results, a classical combined isotropic and kinematic hardening constitutive model, the Armstrong and Frederick (A-F) model is identified by using the particle swarm optimization (PSO) algorithm. However, the yield plateau region and full-range softening behavior of HSSs under cyclic loading are difficult to be captured by the A-F model. A new constitutive model, termed the HSS-TD model with consideration of the yield plateau and three-stage strength softening, is formulated to simulate the response of HSS steels. The HSS-TD model shows significantly lower errors relative to the conventional A-F model, when assessed relative to test data. Moreover, the limitations of the HSS-TD model including influence of strain history and nonproportional loading are discussed. Graphical abstract: Unlabelled Image Highlights: 25 coupon scale with various loading protocols tests were conducted. A new constitutive model for high strength structural steels was proposed. Particle Swarm Optimization algorithm is used for model calibration.